Impact of Long-COVID in children: a large cohort study - Ziv Hersh; Yiska Loewenberg Weisband; Ariel Bogan; Adir Leibovich; Uri Obolski; Daniel Nevo; Ran Gilad-Bachrach (BMC, 2024)
Abstract Background The impact of long-term Coronavirus disease 2019 (COVID-19) on the pediatric population is still not well understood. This study was designed to estimate the magnitude of COVID-19 long-term morbidity 3-6 months after the date of diagnosis. Methods A retrospective study of all Clalit Health Services members in Israel aged 1-16 years who tested positive for SARS-CoV-2 between April 1, 2020 and March 31, 2021. Controls, who had no previous diagnosis of COVID-19, were one-to-one matched to 65,548 COVID-19-positive children and teens, and were assigned the infection dates of their matches as their index date. Matching included age, sex, socio-economic score, and societal sector. Individuals were excluded from the study if they had severe medical conditions before the diagnosis such as cancer, diabetes, chronic respiratory diseases, and/or abnormal physiological development. Generalized Estimating Equations were used to estimate the associations between COVID-19 and the use of medical services. The analysis focused on the 3-6 months after the infection date. Adjustments were made for demographics and for the use of medical services 6-12 and 3-6 months before the infection date. The latter was necessary because of observed disparities in medical service utilization between the groups before the COVID-19 diagnosis, despite the matching process. Results Statistically significant differences were only found for referrals for mental health services [adjusted relative-risk (RR) 1·51, 95%CI 1·15 − 1·96; adjusted risk-difference (RD) 0·001, 95%CI 0·0006 − 0·002], and medication prescriptions of any kind (RR 1·03, 95%CI 1·01-1·06; RD 0·01 95%CI 0·004 − 0·02). Conclusions The significant increase in medication prescriptions and mental health service referrals support the hypothesis that COVID-19 is associated with long-lasting morbidities in children and adolescents aged 1-16 years. However, the risk difference in both instances was small, suggesting a minor impact on medical services.